The constitutional principle of judicial protection and its implementation in practice - Idrysheva, S.K. (Bulletin of the Karaganda University “Law Series”, 2024)
The article examines various problematic aspects of the implementation of the constitutional principle of judicial protection of violated or disputed civil rights in Kazakhstan, the decline in the level of access to justice that has developed in recent years. Using the example of specific civil cases, the unfounded refusals of courts to accept them on the grounds that they are not subject to consideration in civil proceedings are analyzed. The author substantiates the thesis that the accelerated mass transition to the online format of trials caused by the pandemic, along with positive ones, led to negative consequences due to the unpreparedness of the courts in terms of their technical equipment and the insufficient quality and volume of Internet resources. The issues of active use of conciliation procedures by courts as a mandatory pre-trial stage are critically examined, and various official documents are analyzed to substantiate the author’s theses. It is proposed to provide for more stringent requirements for professional mediators in terms of having a legal education and knowledge of psychology and conflictology. According to the author, the current smart justice system has certain shortcomings that impede access to justice due to systematic technical failures in the system. The article also analyzes other aspects that impede the implementation in practice of the constitutional principle of access to justice. In conclusion, specific options for possible improvement of legislation and the practice of its application on the stated topic are proposed.